The Impact of the Rupiah Exchange Rate, Interest Rates, Inflation, Global Oil Prices, and the Dow Jones Index on the JCI - Lisma Hany; Sobrotul Imtikhanah; Tutut Dwi Andayani (Trescode Green Organization, 2025)
The IHSG is one of the important indicators for investors in making investment decisions. By observing the IHSG, investors can gain a comprehensive overview of the condition and trends of the stock market. By monitoring the IHSG, investors can analyze market potential, risks, and apply appropriate mitigation strategies to prevent negative impacts on their portfolios. This study aims to identify and analyze, as well as obtain empirical evidence of the influence of the rupiah exchange rate, interest rates, world oil price inflation, and the Dow Jones Index on the IHSG both partially and simultaneously. The population of the study consists of data on the rupiah exchange rate, interest rates, world oil price inflation, the Dow Jones Index, and the IHSG from 2019 to 2022. The analytical tool used in this study is multiple linear regression. The results of the study show that the rupiah exchange rate has a negative effect on the IHSG, while interest rates, world oil price inflation, and the Dow Jones Index have a positive effect on the IHSG. Simultaneously, all variables influence the IHSG. The overall influence of all variables on the IHSG is 91.7%.